Dry matter productivity and soil physical properties after winter cover crops cultivation - Deimling, Katiely Aline Anschau; Seidel, Edleusa Pereira; Rosset, Jean Sérgio; Mottin, Marcos Cesar; Herrmann, Daniela da Rocha; Favorito, Amanda Cecato (Scientia Agraria Paranaensis, 2019)
The present study aimed to evaluate the dry matter yield of cover crops cultivated in monoculture and intercropped in a no-till system and its effects on the soil physical properties. The experimental design was of randomized blocks, with four replicates. Treatments used were black oat, black oat + forage radish, forage radish, black oat + field pea, field pea and the control (fallow). After 100 days after sowing the cover crops, the dry matter yield was evaluated, with the highest values found in the intercropped crops. After desiccation, undeformed soil samples were collected for the determination of macroporosity, microporosity, total porosity and soil bulk density in the 0 - 0,10; 0,10 - 0,20; 0,20 - 0,30 and 0,30 - 0,40 m layers. Soil penetration resistance was evaluated with a digital penetrometer. The intercrop of black oat with field pea and with forage radish provided the highest dry matter yield, showing the potential of dry matter accumulation in relation to monoculture. The cover crops were capable of improving the macroporosity, bulk density and soil penetration resistance when compared to the fallow area (control); however, they had no influence in soil aggregation due to the high compaction degree in the area.